Krisis Intelektual Mahasiswa Pendidikan Agama Islam dalam Pemanfaatan Platfrom Artificial Intelligence (CHATGPT) di Universitas Islam Zainul Hasan Genggong Probolinggo - Ika Feronika; Kustiana Arisanti; Nur Amin (Kartika: Jurnal Studi Keislaman, 2026)
This research is motivated by the development of Artificial Intelligence, particularly ChatGPT, which has influenced the learning process of students at Universitas Islam Zainul Hasan Genggong, an institution grounded in Islamic boarding school values. The advancement of this technology has raised concerns regarding the decline of students’ critical thinking skills and intellectual independence. This study aims to analyze the utilization of ChatGPT, its usage patterns, and its impact on students of the Islamic Religious Education Study Program. The research employed a qualitative approach using interview techniques with students and lecturers. The findings indicate that ChatGPT is widely used as an academic support tool due to its convenience, speed, and practicality in assisting with assignments. However, excessive use may lead to dependency, reduced analytical skills, and a decline in the depth of material comprehension. Differences were also found between students who rely heavily on AI and those who study independently, particularly in their ability to explain materials, analytical sharpness, and confidence in expressing critical opinions. In addition, uncontrolled use of AI may reduce students’ interest in reading books and scientific journals. Nevertheless, AI remains beneficial when used proportionally and supported by good digital literacy in order to maintain the quality of academic learning